The Effectiveness of Islamic Counseling Services in the Meaningfulness of Life of Orphans - Saragih, Siti Aisah; Siregar, Alfin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine the meaning of life of orphaned and orphaned students at school and the effectiveness of Islamic counseling services through Islamic counseling services. The method of this research uses quantitative. The population in this study were all students of Ikhlasiyah Guppi Muslimin class XI-1, which amounted to 31 people. The sample in this study were orphaned and orphaned students of Ikhlasiyah Guppi Muslimin using a stratified random sampling technique in determining the sample so as not to overlap with other groups with a sample size of 5 people. This study measured both variables using the meaningfulness of life scale with self-concept. This study uses experimental research with the experimental type (pretest-posttest design). The data collection tool used in this study is a Likert scale. The data analysis technique used is a paired sample T-test. Paired sample T-test is a method to see if a group's improvement is significant after being given a service or treatment. SPSS results through the paired sample T-test test show that in the equal variances assumed column, the Sig (2-tailed) value is 0.001 <0.05, which means that assertive training through Islamic counseling services increases the meaningfulness of life in orphans and orphans.